جريمة التعسف في استعمال أموال الشركة - سهيلة بوهجة; شهرزاد براهمية (My University, 2022)
Summary The offence of abuse of the company's funds is one of the most serious offences that negatively affects the functioning of businesses as the cornerstone of the economy of the world's nations, The Algerian legislature has established the offence of abuse of the company's funds under the provisions of Ordinance No. 75-59, which contains the amended and supplementary commercial law. in addition to provisions contained in Ordinance No. 03-11 on the Monetary and Loan Act, In order to safeguard the company's finances and protect it from any exploitation to which it may be exposed by the manning apparatus imprisonment ", as well as the introduction of aggravated penalties reflected in the deprivation of liberty and other financial penalties, The purpose is to protect the company and partners directly and personally affected by this crime. ................... ملخص تعد جريمة التعسف في استعمال أموال الشركة أحد أخطر الجرائم التي تؤثر سلبا على سير الشركات التجارية ، باعتبار هذه الأخيرة لبنة الأساس التي يقوم عليها اقتصاد دول العالم، وقد أقر المشرع الجزائري جريمة التعسف في استعمال أموال الشركة بموجب أحكام تضمنها الأمر 75-59 المتضمن القانون التجاري المعدل والمتمم ، إلى جانب أحكام تضمنها الأمر رقم 03-11 المتعلق بقانون النقد والقرض، وذلك للحفاظ على الذمة المالية للشركة وحمايتها من أي استغلال يمكن أن تتعرض له من طرف أجهزة التسيير، إضافة لوضع عقوبات مشددة تتجلى في عقوبة سالبة للحرية وأخرى مالية، والغرض من ذلك حماية الشركة والشركاء المتضررين بصفة شخصية ومباشرة من هذه الجريمة . .................... Résumé L’infraction d’abus de fonds de l’entreprise est l’une des infractions les plus graves qui affecte négativement le fonctionnement des entreprises comme pierre angulaire de l’économie des nations du monde, Le législateur algérien a établi l’infraction d’abus de fonds de la société en vertu des dispositions de l’ordonnance n. 75-59, qui contient la loi commerciale modifiée et supplémentaire. en plus des dispositions de l’ordonnance no 03-11 sur la Loi sur les emprunts et les emprunts, afin de protéger les finances de la société et de la protéger de toute exploitation à laquelle elle pourrait être exposée par l’emprisonnement des effectifs ", ainsi que l’introduction de peines plus sévères qui se traduisent par la privation de liberté et d’autres sanctions pécuniaires, Le but est de protéger l’entreprise et les partenaires directement et personnellement touchés par ce crime.